What’s in a Surname? The Effect of Auditor-CEO Surname Sharing on Financial Misstatement - Du, Xingqiang (Journal of business ethics, 2019)
This study examines the influence of auditor-CEO surname sharing (ACSS) on financial misstatement and further investigates whether the above effect depends on hometown relationship and the rarity of surnames, respectively. Using hand-collected data from China, the findings show that ACSS is significantly positively related to financial misstatement, suggesting that the auditor-CEO ancestry membership elicits the collusion and increases the likelihood of financial misstatement. Moreover, ACSS based upon hometown relationship leads to significantly higher likelihood of financial misstatement, compared with ACSS without hometown relationship. Furthermore, the positive relation between ACSS and financial misstatement is more pronounced for rare surnames than for common surnames. The above findings are robust to sensitivity tests on the basis of different measures of ACSS and financial misstatement, and my conclusions are still valid after using the propensity score matching approach to address the endogeneity concerns.